Sources of foreign capital flows and the economy of developing countries: An empirical assessment - Abou-Stait, Fouad (JABM JOURNAL of ACCOUNTING - BUSINESS & MANAGEMENT, 2005)
A number of empirical studies analyze the relationship between the inflow of foreign capital and domestic saving. The paper aims to examine the differential impact of foreign capital inflows on domestic saving to Egypt during the last three decades. It aims to test the hypothesis of weather DFI, work remittances and official capital inflow and domestic saving are co integrated using Johansson approach, and weather DFI and work remittance and official capital Granger cause domestic saving. The study sheds lights on the trends of the flows of public and private capital to developing countries with a particular reference to Egypt. It represents one of few studies that aim to differentiate between the affect of various types of foreign capital